International consensus on natural orifice specimen extraction surgery (NOSES) for colorectal cancer. (23rd January 2019) - Guan, Xu; Liu, Zheng; Longo, Antonio; Cai, Jian-Chun; Tzu-Liang Chen, William; Chen, Lu-Chuan; Chun, Ho-Kyung; Manuel da Costa Pereira, Joaquim; Efetov, Sergey; Escalante, Ricardo; He, Qing-Si; Hu, Jun-Hong; et al.
Abstract: In recent years, natural orifice specimen extraction surgery (NOSES) in the treatment of colorectal cancer has attracted widespread attention. The potential benefits of NOSES including reduction in postoperative pain and wound complications, less use of postoperative analgesic, faster recovery of bowel function, shorter length of hospital stay, better cosmetic and psychological effect have been described in colorectal surgery. Despite significant decrease in surgical trauma of NOSES have been observed, the potential pitfalls of this technique have been demonstrated. Particularly, several issues including bacteriological concerns, oncological outcomes and patient selection are raised with this new technique. Therefore, it is urgent and necessary to reach a consensus as an industry guideline to standardize the implementation of NOSES in colorectal surgery. After three rounds of discussion by all members of the International Alliance of NOSES, the consensus is finally completed, which is also of great significance to the long-term progress of NOSES worldwide.